Assessment of the relationships between physical and motor features of young wrestlers from Turkey - Acar, S.; Koca Ozer, B. (Journal of Anthropology of Sport and Physical Education, 2020)
Physical development, fitness and motor skills are the most important components in determining the performance and success of wrestlers, with wrestling largely dependent on overall body strength and relatively short match times. The aim of the present study is to evaluate the relationships between the physical and motor characteristics of young wrestlers in Sivas, Turkey. The study conducted on 86 male freestyle wrestlers aged 10 to 21 years representing urban and rural areas. The sample was analyzed by age groups; 10 to 14 years olds, 15 to 17 years olds and 18 to 21 years olds due to the skill level of the United World Wrestling (UWW) sport categories. Anthropometric measurements (height, weight, skin folds and body composition) as well as motor tests (speed, flexibility and durability) were performed and the data were analyzed using the Statistical Package for Social Science (SPSS) version 23. The results showed that physical properties were correlated significantly with motor features and affected them significantly. According to standardized regression coefficients (ß), particularly muscle mass and free fat mass values were presented significant relationships on the anthropometric characters for all of age groups. As a conclusion, wrestlers from all age groups have presented with high level of fat mass, muscle mass and fat free mass where motor and physical properties are highly correlated among the wresting athletes in accordance with the special traning methods.